Advantages and disadvantages of buying a home mortgage - Pishna, О.; Gritsenko, O. (Ways to Improve Construction Efficiency, 2018)
The article deals with the actual issue of mortgage lending in Ukraine. The housing issue is an acute issue nowadays and there are many risky points when signing a bank agreement. There is no consensus among scientists on the definition and classification of a mortgage. The comparative characteristics of the types of loan repayments make it possible to determine the optimal first payment option and the subsequent payment system. Efinition of the concept of mortgage its structure and comparison with respect to different banking structures. The problem of housing construction, mechanisms and instruments of its financing in Ukraine is actively discussed. This is particularly true of the crisis conditions under which the country is now developing. The work of leading domestic and foreign economists and financiers is devoted to the study of the problem of mortgage lending. The theoretical basis of this study was the works of Ukrainian scientists, such as: Timofeev VV, Lagutin VD, Busel VT, Vladichin VV, Yurkevich OM. Construction is one of the most promising industries that can turn people and businesses into high-yield investment resources. Thus, due to the development of the construction industry, several problems of modern Ukraine can be solved - social (providing housing for the population), financial (attracting the necessary investment resources to the country's economy), production (development of related industries such as construction materials production and others).